Bioanalytical LC-QTOF/MS Method for a N-phenylpiperazine Derivate (LQFM05): An Anxiolytic- and Antidepressant-like Prototype Drug Applied to Pharmacokinetic and Biodistribution Studies - Ana Cláudia M. Ramos; Kênnia R. Rezende; Carolina M. Teixeira; Aline R. Fernandes; Heloa Santos; Rúbia Darc Machado; Ricardo Menegatti; Boniek G. Vaz; Andréa R. Chaves (MDPI AG, 2023)
The LQFM05 is a prototype drug designed for treatment of psychiatric disorders, such as schizophrenia, exhibiting anxiolytic- and antidepressant-like (12 or 24 µmol/kg) effects in classical behavioral tests. In order to evaluate its pharmacokinetic properties, a liquid chromatography method coupled to a quadrupole time of flight mass spectrometry system (LC-QTOF/MS) was developed and fully validated for LQFM05 analysis in rat plasma and tissue samples (brain, heart, liver, and kidneys). Liquid-liquid extraction, solid phase extraction and protein precipitation were assessed as clean-up procedures for biological samples and analyte enrichment. Plasma and tissue samples underwent protein precipitation as a preliminary step, using acetonitrile. Linearity was fully demonstrated for the dynamic range (10.0 to 900.0 ng/mL), with r2 values higher than 0.99 (RSDslope ≤ 2%, Fcal < Ftab, Ccal < Ctab). Biodistribution studies in rats revealed high brain tissue concentrations (12.4 µg/g), suggesting elevated drug affinity to the main therapeutic target tissue, showing a blood partition coefficient of 1.9. Kidneys also showed great exposure and tissue affinity, suggesting a potential extrahepatic clearance. Likewise, all examined tissues exhibited satisfactory LQFMF05 distribution. The mass fragmentation spectrum indicated the presence of its main metabolite, LQFM235, yielded by high hepatic hydroxylation route, an equally bioactive derivative. Lastly, the developed LC-QTOF/MS method was shown to be sensitive (LOQ = 10 ng/mL), precise and accurate for LQFM05 determination in tissue homogenates and plasma samples.